2023
DOI: 10.1080/0886022x.2023.2172432
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following the first, second and third doses of a COVID-19 vaccine in hemodialysis patients

Abstract: Background This study aimed to identify adverse events following the first three doses of COVID-19 vaccines in hemodialysis (HD) patients. Risk factors associated with postvaccination adverse events were explored. Methods Postvaccination adverse events in 438 HD patients who received 3 doses of COVID-19 vaccines were prospectively assessed. The adverse events among three doses were compared using generalized linear mixed models. Factors associated with adverse events we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…As with previous vaccinations, patients either reported no adverse events or primarily local pain at the injection site. This is in line with previous reports of COVID-19 vaccine tolerability and also extends to other vaccine types 35 . Reactogenicity was significantly different from immunocompetent controls where more individuals reported local and/or systemic reactions that were most frequently pain at the injection site followed by fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…As with previous vaccinations, patients either reported no adverse events or primarily local pain at the injection site. This is in line with previous reports of COVID-19 vaccine tolerability and also extends to other vaccine types 35 . Reactogenicity was significantly different from immunocompetent controls where more individuals reported local and/or systemic reactions that were most frequently pain at the injection site followed by fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…As with previous vaccinations, patients either reported no adverse events or primarily local pain at the injection site. This is in line with previous reports of COVID-19 vaccine tolerability and also extends to other vaccine types 43 . Reactogenicity was significantly different from immunocompetent controls where more individuals reported local and/or systemic reactions that were most frequently pain at the injection site followed by fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…AEs during the early period at 3-day and 7-day post-vaccination were reported to be mild, as demonstrated. The observed AE profile is like those reported in previous COVID-19 vaccine studies [27,28]. The most common AE reported in our study was injection site pain, reported by approximately half of SOT recipients who obtained vaccination.…”
Section: Discussionsupporting
confidence: 87%